A pilot randomized controlled trial of telephone intervention to increase Breast Cancer Screening uptake in socially deprived areas in Scotland (TELBRECS). (September 2016) - Chambers, Julie A; Gracie, Kerry; Millar, Rosemary; Cavanagh, Julie; Archibald, Debbie; Cook, Alan; O'Carroll, Ronan E
Objectives: To determine whether a brief telephone support intervention could increase breast cancer screening uptake among lower socio-demographic women in Scotland, via eliciting and addressing barriers to screening attendance. Methods: In a pilot randomized controlled trial, participants receiving a reminder letter for a missed screening appointment (February-June 2014) were randomized to four arms: No telephone call (control), Simple telephone reminder (TEL), Telephone support (TEL-SUPP), or Telephone support plus anticipated regret (TEL-SUPP-AR). Primary outcomes were making an appointment and attending breast screening. Results: Of 856 women randomized and analysed on intention-to-treat basis, compared with controls, more women in the telephone intervention groups made an appointment (control: 8.8%, TEL: 20.3%, TEL-SUPP: 14.1%; TEL-SUPP-AR: 16.8%, χ 2 (3) = 12.0, p = .007) and attended breast screening (control: 6.9%, TEL: 16.5%, TEL-SUPP: 11.3%; TEL-SUPP-AR: 13.1%, χ 2 (3) = 9.8, p = .020). Of 559 women randomized to the three telephone groups, 404 were successfully contacted and 247 participated in the intervention. Intervention participants (ie. per protocol analysis) were more likely to make (17% versus 10%, χ 2 (1) = 7.0, p = .008) and attend (13% versus 7%, χ 2 (1) = 5.5, p = .019) an appointment than non-participants, but there were no differences in attendance between the three telephone groups. Conclusions: A simple telephone reminder doubled attendance at breast screening in women from lower socio-demographic areas who had not attended their initial appointment, compared with a reminder letter only (odds ratio 2.12, 95% CI (1.2, 3.8)). However, contacting women proved problematic and there was no additional effect of telephone support or anticipated regret.